On Numerical Solution of Quasilinear Boundary Value Problems with Two Small Parameters (Journal of Computational Mathematics, 2021)
We consider the singular perturbation problem $$-ε^2u"+μ b(x,u)u'+c(x,u)=0,u(0),u(1)$$ given with two small parameters $ε$ and $μ$ , $μ =ε^{1+p},p>0$. The problem is solved numerically by using finite difference schemes on the mesh which is dense in the boundary layers. The convergence uniform in $ε$ is proved in the discrete $L^1$ norm. Some convergence results are given in the maximum norm as well.